Non-indigenous species refined national baseline inventories: A synthesis in the context of the European Union's Marine Strategy Framework Directive. (August 2019) - Tsiamis, Konstantinos; Palialexis, Andreas; Stefanova, Kremena; Gladan, Živana Ničević; Skejić, Sanda; Despalatović, Marija; Cvitković, Ivan; Dragičević, Branko; Dulčić, Jakov; Vidjak, Olja; Bojanić, Natalia; Žuljević, Ante; et al.
Abstract: Refined baseline inventories of non-indigenous species (NIS) are set per European Union Member State (MS), in the context of the Marine Strategy Framework Directive (MSFD). The inventories are based on the initial assessment of the MSFD (2012) and the updated data of the European Alien Species Information Network, in collaboration with NIS experts appointed by the MSs. The analysis revealed that a large number of NIS was not reported from the initial assessments. Moreover, several NIS initially listed are currently considered as native in Europe or were proven to be historical misreportings. The refined baseline inventories constitute a milestone for the MSFD Descriptor 2 implementation, providing an improved basis for reporting new NIS introductions, facilitating the MSFD D2 assessment. In addition, the inventories can help MSs in the establishment of monitoring systems of targeted NIS, and foster cooperation on monitoring of NIS across or within shared marine subregions. Highlights: Refined MSFD baseline inventories of non-indigenous species (NIS) are set in EU. The inventories are given per EU Member State (MS) and MSFD subregion up to 2012. The NIS lists provide a basis for reporting new NIS introductions in EU after 2012. Our work constitutes a milestone for the MSFD Descriptor 2 implementation.